Crystal structure of 2-isopropylthioxanthone, C16H14OS - Liu Jin-Qiang (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C16H14OS, monoclinic, P21 (no. 4), a = 8.1588(5) Å, b = 7.8670(4) Å, c = 10.2161(5) Å, V = 655.70(6) Å3, Z = 2, Rgt(F) = 0.0539, wRref(F2) = 0.1312, T = 290 K.